One-pot sequential diprop-2-ynylation and cycloaddition: An efficient synthesis of novel N, N-bis(1, 2, 3-triazol-4-yl) methylarylamines starting from primary amines. Issue 20 (18th October 2019) - He, Zhu-Jun; Wei, Mei-Hong; Zhang, Xiao-Lan; Chen, Jun-Min; Sheng, Shou-Ri
Abstract: A facile, one-pot synthesis strategy for the tertiary arylamines bearing N, N -bis(1, 2, 3-triazol-4-yl)methyl structure has been developed by sequential diprop-2-ynylation of primary amines with propargyl bromide in the presence of calcium hydride in DMF and [3 + 2] "click" cycloaddition with organic azides promoted by cupric acetate in the mixed DMF-H2 O media. This protocol provides some features, such as high efficiency and regioselectivity, easy operation, and moderate to good product yield (56–84%) with a wide substrate scope under mild conditions. Graphical Abstract: